Does excessive liquidity creation trigger bank failures? - Zuzana Fungáčová; Rima Turk-Ariss; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper introduces the "Excessive Liquidity Creation Hypothesis," whereby a rise in a bank's core liquidity creation activity increases its probability of failure. Russia experienced many bank failures over the past decade, making it an ideal natural field experiment for testing this hypothesis. Using Berger and Bouwman's (2009) liquidity creation measures, we find that excessive liquidity creation significantly increased the probability of bank failure during our observation period (2000?2007). This finding survives multiple robustness checks. Our results further suggest that regulatory authorities can mitigate systemic distress and reduce the costs to society from bank failures through early identification and enhanced monitoring of excessive liquidity creators.
URN:NBN:fi:bof-201408071988
Keywords: G21; G28; 330; liquidity creation; bank failures